Identification of bacteria in the tracheal swabs of farmed ostriches and their effect on the viability of influenza A virus. (November 2021) - Abolnik, Celia; Strydom, Christine; Landman, Debbie; Pieterse, Reneé
Avian influenza surveillance is a requirement for commercial trade in ostrich products, but influenza A viruses (IAVs) have proven difficult to isolate from ostrich tracheal swabs that test positive using molecular methods. We hypothesized that microbes unique to the ostrich trachea propagate in the transport medium after sampling and affect viral viability. We cultured tracheal swabs from 50 ostriches on 4 farms in South Africa, and recovered and identified 13 bacterial, 1 yeast, and 2 fungal species. Dietzia sp. had not been identified previously in the oropharyngeal tract of a bird, to our knowledge. The bacteria were tested for antimicrobial susceptibility, and most aerobic species, except for Streptococcus sp. and Pseudomonas sp., were sensitive to enrofloxacin; all were susceptible to sulfonamide. Virus inhibition experiments determined that ostrich-source Streptococcus sp., Pantoea sp., and Citrobacter freundii produced extracellular metabolites that caused a substantial reduction in the IAV titers of 99.9%. Streptomyces, Corynebacterium, Staphylococcus, Arthrobacter gandavensis, Pseudomonas putida, and Acinetobacter spp. similarly reduced the viability of IAV from 77.6% to 24.1%. Dietzia appeared to have no effect, but Rothia dentocariosa, Rhodotorula spp., and Clostridium spp. slightly increased the viability of IAV by 25.9, 34.9, and 58.5%, respectively.